Peixes de riachos neotropicais : padrões ecomorfológicos, convergência evolutiva e uso de recursos alimentares. - Mise, Fábio Teruo (2012)
Trophic guilds on fish assemblage of streams were determinate in order to examine if interspecific variation in diet are related to body shape. The hypothesis assumed was that morphologically similar species tend to belong in the same trophic guild independently of their taxonomic relationship. The specimens were collected in streams belonging to Pirapó River basin, near Maringá city, Paraná, Brazil (22 ° 30'S / 51 ° 15'W, 23 ° 30'S / 52 ° 15'W). Ecomorphological index were obtained by morphometric measures and areas. Information about species' feeding ecology was obtained by analysis of stomach contents adopting the volumetric method. Ordination Multivariate analysis and correlation's matrices tests were used, respectively, to ordinate species according to morphological (Principal Component Analysis and Discriminant Analysis) and trophic (Correspondence Analysis of the Effect of Removal with bow and Cluster Analysis) similarities, and test the significance between correlation of body shape and use of feeding resources, independently of phylogenetic relationships among species (Mantel test). Seventeen species were analyzed in this study belonging to the orders Characiformes, Siluriformes and Cyprinodontiformes. Seven trophic guilds were characterized according to the similarities in the diet. The Principal Component Analysis showed an ecomorphological segregation gradient related to food type and capture in water column. On one side were Omnivores with a tendency to insectivory, Omnivores with tendency to herbivory and Insectivore. These guilds had species with more compressed bodies, bifurcate caudal fin and larger area of anal fin, which provide greater swim ability in the water column and facilitates the capture of allochthonous items. At the other side of the gradient were Detritivores, with more developed pelvic fins that provide greater efficiency to support the body in benthic region and stretches of fast water. Larvivores, Omnivores and Invertivores with tendency to detritivory occupied intermediate portion of the gradient showing morphological structures that facilitate the exploitation of the substrate and capture of autochthonous items, especially insects and other aquatic invertebrates. Discriminant Analysis classified correctly 92% of trophic guilds according to the morphology, strengthening the predictive character of ecomorphology. Ecomorphological and trophic convergence were observed between phylogenetically distant taxa, as Characidium aff. zebra (Characiformes: Crenuchidae) and Heptapteridae (Siluriformes), characterized in the same trophic guild being close ecomorfologically. The Mantel test corroborated the evidence that morphologically similar species tend to use the same trophic resource, independently of their phylogenetic relationships. Thus the stream fish assemblages studied have an organization in feeding guilds defined by morphology of species, confirming the initial hypothesis.